Online business sustainability and challenges to meet the demands of online consumers - Diyana, Kamarudin; Suhaidah, Hussain; Tengku Auwalul Hawa, Yahya; Nor Suraini, Mohd Hassan (Future Academy, 2019)
Digital entrepreneurship the trend of entrepreneurship, where entrepreneurs are able to sell their items, as the online space seems to be this unique entrepreneurial space for entrepreneurs. Common perceptions seem to be that very little goes into selling items online, where barriers are expected to be low, with low cost equipment and not much time needed. Even brick and mortar shops are selling items online to sustain their business in this ever growing business space. This research delves into what goes on behind the scene for these online entrepreneurs. It also strives to understand consumer behaviours, where it looks at the different platforms that consumers use most and why these platforms are more trusted. This ethnographic case study looks at the digital business from multiple different angles where consumers, entrepreneurs, instructors, along with an online paying platform staff were given open ended surveys, interviewed online and face to face. The purpose of this research is to evaluate the effort entrepreneurs put in, and how much they are getting back, evaluating consumer’s perspectives, and assessing whether entrepreneur practice in the online platform is relevant to what is needed by the consumers. The research implements a micro and macro analysis approach. The micro analysis evaluates different components from the two sets of participants, which are the online shoppers and the online entrepreneurs, with their own separate themes whereas the instructor’s answers and the third party customer service answers were used as a macro analysis.